MAGDALENA KARČIAUSKIENĖ ABOUT THE CONTRIBUTION OF INTERWAR LITHUANIAN DIDACTS TO THE DEVELOPMENT OF PRIMARY EDUCATION SYSTEM IN OUR COUNTRY - Grabauskienė, Antanina (Acta Paedagogica Vilnensia, 2009)
The article discusses Prof. M. Karčiauskienė’s, this year celebrating her 90th birthday, scientific production in which she analyzes at length the theory and methods of primary education, created by interwar Lithuanian didacts. Basically the article relies on her two essential books: “Primary Education Experience in Lithuania (1918–1940)” and “Experience of Primary Reading in 20th century Lithuania”. Having properly analyzed those two works, it is possible to distinguish the following professor’s ideas on the role of interwar Lithuanian educators to the development of Lithuanian primary education not only in interwar period but to present day as well: * in order to improve the system of primary education, it is necessary to rely on teaching classics and national history and traditions, resourcefully combining contemporary things with fundamental theoretical requirements. * integrating the contents of primary education into the teaching process it is necessary to make the native language the pivotal issue, through which not only the linguistic knowledge and skills are acquired, but also the linguistic culture is developed, the child gets a better chance to estimate the phenomena of the world that surrounds him, his ability to think and other moral values are enhanced. * the main assumption to implement the above mentioned expectations of primary education is the proper training of teachers, i.e. the development of their competence and responsibility.